Persaingan Islam dan Kristen di Kota Solo. Sebuah Tinjauan Sejarah - Adif Fahrizal Arifyadiputra (JUSPI (Jurnal Sejarah Peradaban Islam), 2020)
The main problem studied in this study is how the process of Islamization and Christianization took place in Surakarta in the New Order, who are the actors, and what the impact this process. Also how identities take root by this process gave a way for the competition and suspicion between those communities. This article concluded that the socio-political context surrounding Islamization and Christianization in Surakarta and social background of the actors involved in this process have great influence on religious identities that developed and competed in Surakarta.